Effect of sodium chloride, nitrate/nitrite and refrigeration on mycological status of salted Mugil cephalus fish - Jassim, Mohammed Measr Hasan; Dr. Mohammed Abdul Aati Abdullah (IJRDO - Journal of Business Management, 2020)
The aim of the present study was to evaluate the effect of table salt (sodium chloride), nitrate/nitrite mixture and refrigeration on mycological status of laboratory prepared salted fish. Four groups of salted fish (Mugil cephalus) were prepared in the laboratory using 10% table salt, 10% table salt plus refrigeration, 10% table salt plus nitrate/nitrite mixture or 20% table salt. Samples of fish skin from each group were taken at zero, 5, 10, 15, 20 days and ripening point interval and were inoculated on three different media (Dicloran rose Bengal chloramphenicol agar, malt extract medium + 10% NaCl and malt extract medium + 20% NaCl) to be evaluated for their mycological status. The mycological evaluation revealed that a total number of 19 genera, 53 species and one species variety in addition to some unidentified species of yeasts and sterile mycelia were isolated from fish skin samples. Increasing the concentration of table salt used in salting, adding mixture of nitrate/nitrite and refrigeration had inconsistent effects on the total number of fungi recovered on the three used media.